Pregnancy Complications - Pardabaevna, Isroilova Guljannat; Moxinur, Abdulhakimova (International Journal on Integrated Education, 2023)
The article considers pathological conditions in obstetric practice that have arisen in connection with gestation and violate its natural course. At the initial stages, they may not be accompanied by clinical symptoms, subsequently manifested by pain in the lower abdomen, vaginal discharge, impaired fetal movement, headaches, edema.